Physical and Digital Retail: Through the Case of Dior Parfums Boutique in Champs-Élysées - Vázquez Sacristán, Isabel Adriana; Rodríguez Hernández, Marina; Liberal Ormaechea, Sheila (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The current retail situation is analyzed and its development possibilities are assessed through a bibliographic review and interviews with experts on Dior Parfums’ physical and virtual boutique in Champs Élysées. One of the conclusions reached is the importance of ensuring that virtual stores are not simply inert replicas of physical stores, particularly in the case of luxury brands. Thus, a degree of virtualized human assistance would be desirable to ensure a positive, memorable shopping experience that is likely to generate a high level of loyalty.